Multi-Criteria Assessment to Automate Water Treatment Plants Using the Analytical Hierarchy Process - Oddershede-Herrera, A; Macuada-Silva, C (Inderscience Publishers, 2015)
This paper presents a framework to assist in the evaluation of water treatment (WT) plants and water waste treatment (WWT) plants for automation in a metropolitan region in Chile. The different plants offer different attributes, relating to production resources, feasibility and efficiency process. The aim is to determine the most suitable WT and WWT plants for incorporating an automated system during night shifts. The analytical hierarchy process (AHP) is used to develop a new multi-criteria decision model based on expert judgements for identifying high-priority requirements for automating each treatment plant and any corresponding significant implications. The study provides a basis for setting priorities and decision-making for incorporating an automated system to WT and WWT plants at any locality. Copyright © 2015 Inderscience Enterprises Ltd.